Rollinia mucosa (Jacq.) Baillon (Annonaceae) active metabolites as alternative biocontrol agents against the lace bug Corythucha gossypii (Fabricius): an insect pest. - Giraldo-Rivera, Ana Isabel (2018)
The lace bug, Corythucha gossypii (Fabricius) is a serious pest affecting over 24 wild and commercially important plant species of the families Annonaceae, Passiflorcae, Caricaceae, Euphorbiaceae, and Solanaceae. Thus far, commercial insecticides, such as 0.1% Dimethoate and 0.1% Imidacloprid have shown effectiveness against this insect, but no botanical pesticides are available to control this bug. In the present study, a Rollinia mucosa (Jacq.) Baillon ethanol extractwas evaluated as a biological control agent against the lace bug. Through a toxicity assay involving Artemia salina, the median lethal concentration (LC50) of a raw ethanol extract of R. mucosa seeds was determined, as well as that of its Acetogenin (F1) and Alkaloid (F2) fractions; these LC50 were 0.184, 0.082, and 0.0493 g/mL, respectively. In addition, with an insecticide assay on lace bug nymphs, a mortality percentage of 86.67% at 5 g/mL after 72h was observed. These data demonstrate that the R. mucosa seed extract is highly active. Further chemical characterization studies revealed that the main active metabolites contributing to extract activity were acetogenins and alkaloids.